School library day-to-day operations : - Stephens, Claire Gatrell (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2014)
This book provides a straightforward, easy-to-follow procedural manual that will enable school library aides and new school librarians to develop excellent school library collections